2016
DOI: 10.1002/cbin.10594
|View full text |Cite
|
Sign up to set email alerts
|

Nuclear extrusion precedes discharge of genomic DNA fibers during tunicamycin‐induced neutrophil extracellular trap‐osis (NETosis)‐like cell death in cultured human leukemia cells

Abstract: We previously reported that the nucleoside antibiotic tunicamycin (TN), a protein glycosylation inhibitor triggering unfolded protein response (UPR), induced neutrophil extracellular trap-osis (NETosis)-like cellular suicide and, thus, discharged genomic DNA fibers to extracellular spaces in a range of human myeloid cell lines under serum-free conditions. In this study, we further evaluated the effect of TN on human promyelocytic leukemia HL-60 cells using time-lapse microscopy. Our assay revealed a previously… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 10 publications
0
3
0
Order By: Relevance
“…Recent reports showed that differentiation of HL-60 cells, a human promyelocytic leukemia cell line, into mature neutrophils with calcium ionophore, ATRA, or dimethyl sulfoxide or exposure to the glycosyltransferase inhibitor tunicamycin (TM) resulted in the formation of NET-like structures. 22, 23, 24, 25 The nuclei of APL blasts lack lobules and the distribution of chromatin is loose, which are precursors to ET release. In this study, we hypothesized that APL cells are able to form extracellular DNA traps (ETs) and explored conditions under which APL cells are activated.…”
mentioning
confidence: 99%
“…Recent reports showed that differentiation of HL-60 cells, a human promyelocytic leukemia cell line, into mature neutrophils with calcium ionophore, ATRA, or dimethyl sulfoxide or exposure to the glycosyltransferase inhibitor tunicamycin (TM) resulted in the formation of NET-like structures. 22, 23, 24, 25 The nuclei of APL blasts lack lobules and the distribution of chromatin is loose, which are precursors to ET release. In this study, we hypothesized that APL cells are able to form extracellular DNA traps (ETs) and explored conditions under which APL cells are activated.…”
mentioning
confidence: 99%
“…Thus, this alternative cell death process may represent a therapeutic target in the treatment of resistant cases and attenuating apoptosis-associated complications. NET-like structures are also generated in other myeloid cell lines 23 , and ATO is known to exert anticancer effects on other hematopoietic tumor cells 17 , 18 . Further studies are needed to determined whether ATO induces ETosis in other hematological malignancies.…”
Section: Discussionmentioning
confidence: 99%
“…First described as an alternative route of bacterial killing in 2004, the formation of neutrophil extracellular traps (NETs) (ETs) is a process of cell death distinct from apoptosis, which has since been referred to as NETosis 19 21 . Formed mainly by immune cells, ETs can also be released by human leukemia cells when exposed to microorganisms, reactive oxygen species (ROS) or tunicamycin 22 , 23 . Studies from our laboratory have shown that APL cells from patients can also undergo this novel cell death process, producing ETs through autophagy 24 , 25 , that has been linked to the mechanisms of ATO.…”
Section: Introductionmentioning
confidence: 99%